Study of the required thermal insulation (IREQ) of clothing using infrared imaging - Ahmad, Tanveer; Rashid, Taimur; Khawaja, Hassan Abbas; Moatamedi, Mojtaba (Multi-Science Publishing, 2017)
OPEN ACCESS The International Journal of Multiphysics is now Open Access. There will be no submission charges. The Article Processing Charge (APC) is £600. The articles will be published under Creative Commons Attribution License (CC-BY 4.0). The authors will hold the copyrights without restrictions. Accepted manuscript version. Link to publisher's version: http://doi.org/10.21152/1750-9548.11.4.413 The sense of cold develops due to the increase in heat loss from a human body. Excessive cold can be a health hazard, since excessive heat loss from the body may result in hypothermia/frostbite. Decreased body temperature due to heat loss also affects the physical, manual and perceptive performance of individuals. Therefore, protective measures are taken through clothing that controls and regulates heat loss. Clothing is a protective means for thermal insulation. Clothing and garments used in cold climates should have sufficient insulation to maintain the thermal balance of the body. The required clothing insulation (IREQ) is calculated on the basis of the hypothesis concerning the heat flow by conduction, convection, radiation and evaporation. This term is well defined in standards such as BS-EN 342 and ISO 11079:2007 (E). This paper presents an experimental study of the use of state-of-the-art Infrared (IR) thermography to estimate IREQ values. However, real IREQ values are difficult to estimate, considering that parameters, such as individual metabolism, are unknown and subject to change. Therefore, relative IREQ (IREQ*) values are computed and compared. Experiments were also conducted to measure the relative IREQ of winter jackets, summer jackets, and sweaters. The infrared images were obtained using a FLIR® T1030sc camera and analyzed using FLIR® Researcher Max software. The experiments were performed under conditions of -20°C to -35°C in the cold room at UiT- The Arctic University of Norway.